Relationship of Lateral Dentoskeletal Morphology to Dental Crowding in Patients With Class II Malocclusions - Enas T. Al-Jwary; Hind T. Jarjees; Omar H. Alluazy (University of Mosul, College of Dentistry, 2017)
Aims: The aims of this study was to evaluate the relationship of lateral dentoskeletal morphology to the amount of dental crowding in patients with Class II malocclusion. Materials and Methods: Study models and lateral cephalometric radiographs of a Class II malocclusion of 62 Iraqi patients(18-25 years) lived in the center of Mosul City (30males and 32 females), were evaluated. The sample was divided into two groups according to severity of pretreatment mandibular crowding. Group 1 consisted of 30 patients and have crowding ≥ 3 mm. Group 2 have 32 patients and crowding Results: Significant differences between crowding less than 3mm and crowding groups more than 3mm were seen in posterior facial height ( S-Go) , the angle between sella, nasion and occlusal plane line ( S-N-Ocp) and the angle between sella, nasion and the long axis of lower central incisor (S-N-L1) in males, while in females, the significant differences were seen in the angle between sella, nasion and the long axis of lower central incisor (S-N-L1) and the angle between Sella-nasion line and mandibular plane(NS- GoMe). The other parameters showed no significant differences. The correlation coefficients of the amount of crowding with all the measurements were studied. Some of them showed a positive correlation, while others showed a negative one. Conclusions: Subjects with Class II malocclusion and different amount of dental crowding have no significantly relation with skeletal parameters. Results suggest that dental crowding is independent of the skeletal measurements.